2011
DOI: 10.4028/www.scientific.net/amr.367.801
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Gamma Radiation in Automobile Mechanic Workshops in an Area of Benin City, Nigeria

Abstract: Environmental radiation measurement was carried out in several automobile mechanic workshops within Ugbowo area of Benin-City, Edo State, Nigeria. A Digilert 50 Nuclear Radiation monitor was used to ascertain the level of radiation to which these workers are daily exposed. The study revealed that the average annual effective dose rate from these sites is approximately 0.40 mSv/yr which is lower than the value of 1.0 mSv/yr averaged over five consecutive years according to the dose limit placed by the Basic Saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It was observed that the estimated total annual effective dose outdoor for the sites range from 27.3-79.9 μSv y −1 . A Measurement of Gamma Radiation in Automobile Mechanic Workshops was carried out in an area of Benin City, Nigeria (Nworgu et al, 2012). The study revealed that the average annual effective dose rate from these sites is approximately 0.40 mSv/yr which is lower than the value of 1.0 mSv/yr averaged over five consecutive years according to the dose limit placed by the Basic Safety Standards (BSS) SCHEDULE II and the International Commission on Radiological Protection (ICRP) REPORT 60.…”
Section: Determination Of Absorbed and Effective Dose From Natural Bamentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the estimated total annual effective dose outdoor for the sites range from 27.3-79.9 μSv y −1 . A Measurement of Gamma Radiation in Automobile Mechanic Workshops was carried out in an area of Benin City, Nigeria (Nworgu et al, 2012). The study revealed that the average annual effective dose rate from these sites is approximately 0.40 mSv/yr which is lower than the value of 1.0 mSv/yr averaged over five consecutive years according to the dose limit placed by the Basic Safety Standards (BSS) SCHEDULE II and the International Commission on Radiological Protection (ICRP) REPORT 60.…”
Section: Determination Of Absorbed and Effective Dose From Natural Bamentioning
confidence: 99%
“…Automobile Mechanic workshops in most cities in Nigeria could pose serious health hazards to the auto technicians (locally called mechanics). This is as a result of the fact that these mechanics are exposed to metals indiscriminately dumped in the vicinity of the workshop that might have been contaminated by other radioactive metals in the course of production (Nworgu et al, 2012).…”
Section: Determination Of Absorbed and Effective Dose From Natural Bamentioning
confidence: 99%
“…Previous studies have shown that there exist enhanced levels of ionizing radiation due to traces of radionuclides found in books [5], food stuffs [6] and vegetation [7]. Levels of ionizing radiation higher than the normal environmental background levels have been observed in industrial facilities [1, 8 -11], farmlands [12], medicinal plants [13,14], automobile mechanical workshops [15] and building materials [16]. Some fruits and medicinal plants ingested by humans have been observed to contain radioactivity that can raise the level of exposure to ionizing radiation in the environment [17].…”
Section: Introductionmentioning
confidence: 99%
“…Hazards caused by such dumpsite are not only in term of odor and presence of disease causing microorganism, but can arise from the radiation emanating from such dumpsite [18] . Various radioactivity measurements have shown the existence of traces of radionuclide in books [19] and in the staple food consume in Nigeria [20] . It has also been established that vegetation and environmental fields in Nigeria contain traces of radioisotopes.…”
Section: Introductionmentioning
confidence: 99%